2021
DOI: 10.1039/d1nr01422f
|View full text |Cite
|
Sign up to set email alerts
|

A high-voltage non-aqueous hybrid supercapacitor based on the N2200 polymer supported over multiwalled carbon nanotubes

Abstract: P(NDI2OD-T2), also known as Polyera ActivInk N2200, is a widely accepted non-fullerene acceptor polymer that figures prominently in the energy harvesting application due to its ease of synthesis, high electron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Our research group recently reported a modified Stille approach for synthesizing P(NDI2OD-T2) by carrying out the polymerization in the high boiling solvent t-butyl toluene (TBT) at a temperature of 160 1C (batch process), which resulted in a high molecular weight polymer in very short time of 2 h or less. 38 The observed molecular weight was M n : 188 kDa, and molar-mass dispersity (Ð M ): 3.1 as determined by SEC using THF as the eluent and PS as standards. This considerably shortened polymerization time was unlike the 72 h usually reported in the literature for the synthesis of similar polymers by the Stille route.…”
Section: Stille Polymerization (E)mentioning
confidence: 99%
“…Our research group recently reported a modified Stille approach for synthesizing P(NDI2OD-T2) by carrying out the polymerization in the high boiling solvent t-butyl toluene (TBT) at a temperature of 160 1C (batch process), which resulted in a high molecular weight polymer in very short time of 2 h or less. 38 The observed molecular weight was M n : 188 kDa, and molar-mass dispersity (Ð M ): 3.1 as determined by SEC using THF as the eluent and PS as standards. This considerably shortened polymerization time was unlike the 72 h usually reported in the literature for the synthesis of similar polymers by the Stille route.…”
Section: Stille Polymerization (E)mentioning
confidence: 99%
“…In some cases, the polymer composite contains an inorganic nano‐filler (SiO 2 , AlO 3 , MgO, etc) inside a polymer matrix. The inorganic filler increases the polymer dielectric properties but, they are not the most environmental‐friendly option so, all‐polymeric (polymeric composites with organic fillers) electrodes and electrolytes are emerging due to the advantages that they provide 121,122 …”
Section: Polymer and Polymer Composites For Batteries Obtaining And T...mentioning
confidence: 99%
“…The inorganic filler increases the polymer dielectric properties but, they are not the most environmental-friendly option so, all-polymeric (polymeric composites with organic fillers) electrodes and electrolytes are emerging due to the advantages that they provide. 121,122 All-polymeric composites have good cycling stability, high power densities, and their capacitance increases due to the higher porosity of the conductive polymers. 50 They usually develop a high flexibility, but it comes at the expense of the electrical conductivity so, the optimal point between enhanced mechanical and electrical properties should be found.…”
Section: Last Developments In Polymer Composites For Energy Storage D...mentioning
confidence: 99%
“…[20] Some additional reports on similar types of D-A polymers for energy storage applications are summarized in Table S1 (Supporting Information). [16,[26][27][28][29][30][31] Although a few D-A CPs have exhibited moderate performances, significant efforts are still required to develop efficient CPs with novel molecular designs as electrode materials for practical applications.…”
Section: Introductionmentioning
confidence: 99%